Imunoterapia contra pitiose: caracterização molecular de isolados brasileiros de Pythium insidiosum - Azevedo, Maria Isabel de (2011)
The Pythium insidiosum is an aquatic oomycete that is the causative agent of pythiosis, an important disease in humans and animals that is prevalent in tropical and subtropical areas. In Brazil it was first reported in 1974, then several cases this disease has been reported throughout the country. The failure in the antifungal therapy combined with cases unresponsive to immunotherapy existing, lead to molecular studies in order to investigate possible genetic variations among Brazilian isolates, and this may be able to contribute on the research for the improvement of immunotherapy available. Thus, this study aimed to evaluate the genetic diversity of thirty P. insidiosum isolates from different regions of Brazil, and compare all of them with isolates from Thailand, one isolate from Central America and another isolate from North America, by sequencing and the analysis of genomic DNA regions corresponding to cytochrome c oxidase (COX II) and ITS1, 5.8S rRNA and ITS2 rDNA (ITS). The analyses of nucleotide sequences of both regions were carried out, individually and in combination, using the following methods: Maximum parsimony (MP); Neighbor-joining (NJ); Maximum likelihood (ML); and Bayesian analysis (BA). Our data demonstrated all of P. insidiosum isolates as monophyletic in relation to the other Pythium species. Analises of COX II gene sequences subdivided P. insidiosum isolates into three groups, whose arrangement provides the Thai isolates as paraphyletic in relation to the Brazilian isolates. The molecular analyses performed in this study suggest an evolutionary proximity among all of American isolates, including the Brazilian, from Costa Rica and from the United States, that were grouped in a single group. COX II gene network analysis showed signs of a recent expansion of P. insidosum isolates, probably originated from the Asiatic to America continent. By analysis of COX II gene demonstrated the highest levels of genetic variability among P. insidiosum isolates studied in here, additionally, the highest levels of phylogenetic information were shown, when it was compared to the ITS region analysis. Nevertheless, both genetic markers selected for this study proved to be entirely congruent in the phylogenetic relations among Brazilian isolates of P. insidiosum, since clustered all of them into a single monophyletic group which did not shown to have genetic variability. The results indicate that the strain used in the production of the immunotherapic - Pitium-Vac ® - is representative of the Brazilian isolates of P. insidiosum.